1994
DOI: 10.1007/bf00019048
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between chlorophyll fluorescence quenching and the quantum yield of electron transport in isolated thylakoids

Abstract: The relationship between the empirical fluorescence index ΔF/Fm' and the quantum yield of linear electron flow, Φ(s), was investigated in isolated spinach thylakoids. Conditions were optimised for reliable determination of ΔF/Fm' and Φ(s) with methyl viologen or ferricyanide as electron acceptors under coupled and uncoupled conditions. Ascorbate in combination with methyl viologen was found to stimulate light-induced O2-uptake which is not reflected in ΔF/Fm' and interpreted to reflect superoxide reduction by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…The relationship between the two efficiencies became non-linear at the higher quantum yields or at low measuring PFD (data not shown). This non-linearity could be due to several factors such as the different populations of cells seen by the fluorescence measurement and the gas exchange, inaccuracies in determining respiration in the light, the presence of cyclic electron transport around PSII (Genty 1989) or due to inactive PSII centres (Hormann et al 1994). The calculated rates of total non-cyclic electron flow J~, electron transport allocated to CO2 fixation, JA, and electron transport allocated to 02 reduction, JL, as a function of PFD are shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The relationship between the two efficiencies became non-linear at the higher quantum yields or at low measuring PFD (data not shown). This non-linearity could be due to several factors such as the different populations of cells seen by the fluorescence measurement and the gas exchange, inaccuracies in determining respiration in the light, the presence of cyclic electron transport around PSII (Genty 1989) or due to inactive PSII centres (Hormann et al 1994). The calculated rates of total non-cyclic electron flow J~, electron transport allocated to CO2 fixation, JA, and electron transport allocated to 02 reduction, JL, as a function of PFD are shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Hormann et al (1994) and Schreiber et al (1995a) demonstrated a linear relationship between ap and (Dp, at high irradiances but a deviation from nonlinearity at high quantum efficiencies, i.e. at low irradiances.…”
Section: Discussionmentioning
confidence: 92%
“…high quantum yields) and are ascribed to the presence of PSI1 heterogeneity (e.g. Schreiber et al 1995a;Hormann et al 1994). However, microalgae have a more flexible photosynthetic machinery and can more easily adjust their optical properties.…”
Section: Discussionmentioning
confidence: 99%
“…It is reminiscent of the 'Genty' plot of 1-Fs/Fm' against the quantum yield of oxygen evolution during short-term steady illumination (Genty et al 1989), where Fs is the steady-state fluorescence yield and Fm' the maximum fluorescence yield during illumination, and the parameter 1-Fs/Fm' represents the average quantum efficiency of PSII photochemistry during illumination. An empirical relationship, linear in high irradiances but asymptotic in the low irradiance (high quantum yield) region, has been reported in leaves (Seaton and Walker 1990; and thylakoids (Hormann et al 1994). In the low-irradiance region, the loss of quantum yield of oxygen evolution without appreciable decline of 1-Fs/Fm' has also been interpreted to mean the loss of a sub-population of PSII which contributes little to the flu-orescence parameter in thylakoids (Hormann et al 1994).…”
Section: Heterogeneity Of Psii As Revealed By Measurements Of Chloropmentioning
confidence: 95%